2016
DOI: 10.1038/srep31576
|View full text |Cite
|
Sign up to set email alerts
|

First Comprehensive Proteome Analyses of Lysine Acetylation and Succinylation in Seedling Leaves of Brachypodium distachyon L.

Abstract: Protein acetylation and succinylation are the most crucial protein post-translational modifications (PTMs) involved in the regulation of plant growth and development. In this study, we present the first lysine-acetylation and lysine-succinylation proteome analysis of seedling leaves in Brachypodium distachyon L (Bd). Using high accuracy nano LC-MS/MS combined with affinity purification, we identified a total of 636 lysine-acetylated sites in 353 proteins and 605 lysine-succinylated sites in 262 proteins. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
86
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(92 citation statements)
references
References 61 publications
6
86
0
Order By: Relevance
“…Although a number of proteins in the pathways of carbon fixation, photosynthesis and oxidative phosphorylation were found to be succinylated in both common wheat (Additional file 1: Figure S4b, Additional file 2: Table S6) and B. distachyon [13], few common proteins were identified between them. Moreover, succinylated proteins associated with peroxisome were only identified in common wheat (Additional file 1: Figure S4b, Additional file 2: Table S6), and modified proteins related to microbial metabolism in diverse environments and biosynthesis of antibiotics were only found in B. distachyon [13]. These results suggest that lysine succinylation plays both common and specific roles in different plant species.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Although a number of proteins in the pathways of carbon fixation, photosynthesis and oxidative phosphorylation were found to be succinylated in both common wheat (Additional file 1: Figure S4b, Additional file 2: Table S6) and B. distachyon [13], few common proteins were identified between them. Moreover, succinylated proteins associated with peroxisome were only identified in common wheat (Additional file 1: Figure S4b, Additional file 2: Table S6), and modified proteins related to microbial metabolism in diverse environments and biosynthesis of antibiotics were only found in B. distachyon [13]. These results suggest that lysine succinylation plays both common and specific roles in different plant species.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…In animals, succinate can indirectly stabilize the 1a subunit of the transcriptional regulator hypoxia-inducible factor, and succinylation, which relies on succinyl-CoA as substrate, regulates TCA cycle and glycolytic enzymes (Mills and O'Neill, 2014). Interestingly, proteins active in the TCA cycle and glycolysis have also been found succinylated in tomato (Solanum lycopersicum), wheat (Triticum durum), rice (Oryza sativa), and Brachypodium, suggesting a conserved role of succinate and succinyl-CoA in the regulation of metabolic processes (He et al, 2016;Jin and Wu, 2016;Zhen et al, 2016;Zhang et al, 2017c). Other posttranslational modifications such as protein phosphorylation (e.g.…”
Section: Posttranslational Modification Of Proteinsmentioning
confidence: 99%
“…During germination, rice seed undergoes dynamic rearrangements of metabolism and succinylation status if its proteome changes [75]. It was shown that, in rice seedlings, succinylated proteins are enriched in functional categories such as citrate cycle, glycolysis/gluconeogenesis, ribosome, and carbon fixation with notably high coverage in pathways involved in the conversion of glucose to pyruvate [76]. The seedling leaves of Brachypodium distachyon , a grass family plant also exhibited the PTM in carbon metabolism pathways [76].…”
Section: Systems For Post-translational Modifications In Crops Undmentioning
confidence: 99%
“…It was shown that, in rice seedlings, succinylated proteins are enriched in functional categories such as citrate cycle, glycolysis/gluconeogenesis, ribosome, and carbon fixation with notably high coverage in pathways involved in the conversion of glucose to pyruvate [76]. The seedling leaves of Brachypodium distachyon , a grass family plant also exhibited the PTM in carbon metabolism pathways [76]. According to the comparison of succinylated proteins across species by Zhen et al, a high degree of conservation of succinylation was suggested among eukaryotes including humans, E. coli , and plants [75].…”
Section: Systems For Post-translational Modifications In Crops Undmentioning
confidence: 99%
See 1 more Smart Citation